Defining an Architectural Design Strategy for Energy Performance-A Systematic Approach for Students - Mokhtar, Ahmed (2012)
Managing the energy performance of a building should start from the pre-conceptual design phase. Architects at this phase need to analyze the nature of the site environment, the nature of the building, and the comfort requirements of the occupants. An accurate analysis of these elements helps them formulate a design strategy for optimizing energy performance. However, this requires good understanding of the energy behavior of buildings. Such understanding optimally starts at the undergraduate architecture education. This paper presents a systematic approach to construct such understanding through a required course in an architectural curriculum. The paper explains the subjects covered in the course for a student to grasp the fundamentals of analyzing a project from an energy performance point of view. It also explains how to help students manipulate environmental forces and create a building's form that supports optimizing its energy performance. Finally, it discusses the common difficulties to propagate this systematic approach through the rest of the curriculum.